Familial aspects of fear of cancer recurrence: current insights and knowledge gaps - Faraji, Aida; Dehghani, Mohsen; Khatibi, Ali (Frontiers in Psychology, 2023)
Fear of cancer recurrence is fear or worry about cancer recurrence or progress. Fear of recurrence can impact patients' quality of life and wellbeing. Cancer survivors' families support them practically and emotionally, making them a vital supplement for official healthcare. Given the well-established important role of the family in dealing with cancer, we compiled the studies that examined the relationship between family-related factors and fear of cancer recurrence (FCR) among cancer survivors (CSs). One of the foremost studies in this field is the FCR model presented by Mellon and colleagues, which included concurrent family stressors and family-caregiver FCR as factors linked to survivor FCR. Our goal was to prepare the ground for a family-based model of FCR that is more comprehensive than the one proposed by Mellon et al. sixteen years ago. The studies included those with samples of adult cancer survivors from different regions of the world. Most of the studies we reviewed are cross-sectional studies. We categorised family-related factors associated with survivor FCR into partner-related factors, including subgroups of disclosure to partner, cognitions of partner, and partner's sources of support; parenthood-related factors, including having children and parenting stress; family-related factors, including living situation, family history of cancer, family's perception of the illness, and family characteristics; and social interactions including social support, disclosure, social constraints, and attitudes of others. This review sheds light on how significant others of cancer survivors can affect and be affected by cancer-related concerns of survivors and emphasises the necessity of further investigation of family-related factors associated with FCR.